Gertrude Stein Has Arrived : The Homecoming of a Literary Legend - Morris, Roy, Jr (Book collections on Project MUSE., 2019)
"A focused biography, this book details the celebrated author and expatriate Gertrude Stein in her triumphant homecoming to America in 1934, following the surprise success of her disguised memoir, The Autobiography of Alice B. Toklas, the previous year. The book shows how Stein's first visit to America in thirty years renewed her emotional and artistic connection to her homeland"--